FACTORS INFLUENCING COLLECTION OF BLOOD DONOR TEST RESULTS IN NAIROI COUNTY - A CASE STUDY OF NAIROBI REGIONAL BLOOD TRANSFUSION CENTER - Gititu, George; Oluoch, Musa; Tenambergen, Dr. Wanja (Journal of Health, Medicine and Nursing, 2018)
Background: The Kenya National Blood Transfusion Services screens all donated blood for HIV, Hepatitis B&C and syphilis with each blood donor being informed of testing of his or her donated blood and availability of test results for collection at the Regional Blood Transfusion Centers. The study-assessed factors influencing collection of blood test results by blood donors as only less than 10% blood donor's return to collect their test results. Method: The study utilized descriptive cross-sectional study approach employing a mix of both quantitative and qualitative approach. 385 blood donors and seven key informants interviewed using a pre-designed questionnaire and Key informant respectively. Quantitative data was analyzed using Epi info 6.04 while qualitative data was transcribed and analyzed using content thematic framework approach. Results: 95% of participants did not return to collect their test results with 90% not being aware that test results are available for collection. 50% of those who had not collected their test results would not have collected even after being adequately informed. 93% would not collect their test results in presence of friends fearing stigmatization and would not share the outcome of the test even with their families. Conclusion: The study concluded that the collection of donor test results is greatly influenced by knowledge, location of result collection sites, working hours of collection sites, stigma and cultural beliefs. The Study recommends mass sensitization on availability of test results, where to collect results and demystify social cultural beliefs.